2023
DOI: 10.3233/jad-220600
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Heterogeneity of Mild Cognitive Impairment Identified Based on Multi-Modal Data Analysis

Abstract: Background: Mild cognitive impairment (MCI), a prodromal phase of Alzheimer’s disease (AD), is heterogeneous with different rates and risks of progression to AD. There are significant gender disparities in the susceptibility, prognosis, and outcomes in patients with MCI, with female being disproportionately negatively impacted. Objective: The aim of this study was to identify sex-specific heterogeneity of MCI using multi-modality data and examine the differences in the respective MCI subtypes with different pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A clustering study of MCI participants based on multimodal factors identified sex‐specific groups of differing prognoses. 289 In the worst prognosis group, there were almost twice as many female than male APOE ε4 carriers, suggesting that the ε4 allele has a disproportionately detrimental effect in women. Women had a greater association between whole brain atrophy and functional decline than men, and female ε4 carriers had the greatest functional decline for a given level of whole brain atrophy.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 95%
See 1 more Smart Citation
“…A clustering study of MCI participants based on multimodal factors identified sex‐specific groups of differing prognoses. 289 In the worst prognosis group, there were almost twice as many female than male APOE ε4 carriers, suggesting that the ε4 allele has a disproportionately detrimental effect in women. Women had a greater association between whole brain atrophy and functional decline than men, and female ε4 carriers had the greatest functional decline for a given level of whole brain atrophy.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 95%
“…A clustering study of MCI participants based on multimodal factors identified sex‐specific groups of differing prognoses 289 . In the worst prognosis group, there were almost twice as many female than male APOE ε4 carriers, suggesting that the ε4 allele has a disproportionately detrimental effect in women.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 99%
“…AD is associated with progressive decline in memory, executive, and other cognitive functions leading to functional decline and can manifest with diverse clinical presentations and heterogeneity ( Murray et al, 2011 ; Atri, 2019 ; Knopman et al, 2021 ). Sex differences in AD have been shown to contribute to this heterogeneity and affect prevalence, risks factors, disease trajectories, and outcomes ( Nebel et al, 2018 ; Katabathula et al, 2022 ). Depression is a frequent neuropsychiatric symptom that affects many patients with AD and has been shown to be more prevalent in women in the general population as well as in dementia ( Lovheim et al, 2009 ; Chi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%